Work participation and health-related characteristics of sickness absence beneficiaries with multiple somatic symptoms. (April 2016) - Momsen, A.H.; Nielsen, C.V.; Nielsen, M.B.D.; Rugulies, R.; Jensen, C.
Abstract: Objectives: The primary aim was to study whether high levels of multiple symptoms influenced sick-listed individuals' employment status or desire to return to work (RTW) and whether this was associated with social relations at work. Study design: A cross-sectional study nested in a clinical trial. Methods: In 2011–2012, 736 (34%) of 2172 sick-listed individuals completed a posted questionnaire and were included. Main outcome was self-reported employment status. The Symptom Check List (SCL-SOM)'s sum score (0–48) was categorized in high (>18) and low (≤18) levels. Previous employment, sick-listing, and use of health care were register-data. Multivariate logistic regression analyses with adjustments were performed. Results: Beneficiaries with high SCL-SOM score (n = 218, 33%) reported poorer health, job satisfaction, a lower desire to RTW and more problems with supervisors. The risk of being unemployed was higher for this group than for those with a low score. Adjusting for general health reduced the association between symptoms and unemployment, whereas problems with social relations only affected it marginally. Conclusions: Sick-listed individuals reporting high levels of symptoms were more often unemployed and less frequently desired to RTW than those with few symptoms. The association could not be explained by problems with social relations at work. Trial registrations: ISRCTN43004323, and ISRCTN51445682. Highlights: Multiple symptoms are prevalent and problems regarding RTW after long-term sickness absence are a public health issue. Recognition of multiple symptoms in sick-listed may be important in order to prevent permanent withdrawal from the labour market. Those with multiple symptoms reported poorer general health, work ability and job satisfaction compared to those with few symptoms. They experienced less desire to RTW and support from supervisors and were at higher risk of unemployment during sick leave. Associations with less desire to RTW and support could not be explained by problems with their supervisors or co-workers.